Harderian gland of flying and non-flying birds: morphological, histological, and histochemical studies - Rasha R. Beheiry; Sozan A. Ali; Mohamed Aref; Hassan Emam (Journal of Basic and Applied Zoology, 2020)
Abstract Background The aim of the present study is to describe the morphological and histological features of Harderian gland (HG) in long-legged wadding bird (ibis) and different domestic birds (duck, goose, and pigeon). The HG of forty adult male and female from the four avian species constituted the material of the study. Result The HG extended from the optic nerve to the rostral part of the eyeball presents two extremities, one posterior and other anterior, from which the excretory duct was arisen. Between two extremities of the gland, middle groove is present in case of duck and geese, while middle isthmus is present in case of ibis. In pigeon, the gland appeared pointed oval in shape. Microscopically, the HG was multilobular; each lobule was composed of secretory acini that were lined by a single layer of columnar epithelium. In all studied birds, a single duct located centrally with an irregular lumen. In goose, there were crypts along the duct while in duck, the central lumen had villi-like folds projected into the central canal of the tubules. In ibis, the irregular lumen was narrow and elongated while in pigeon, the gland had a central cavity that collected the secretion from tubules arranged radially around the cavity; also, the gland mainly contained both acidic and neutral mucopolysaccharides. Conclusion This work revealed that the histological structure of HG in the four avian species showed characteristic features and thus explained the relationship between their habits and behavior on the structure of this gland.